Entre le réel et l’insolite : l’image du Maroc contemporain dans la prose de Tahar Ben Jelloun entre 1994 et 2009 - Magdalena Zdrada-Cok (Carnets)
The article is dedicated to three novels by Tahar Ben Jelloun: L’Homme rompu (1994), Partir (2006) and Au pays (2009). Being a result of the author’s sociological and journalistic interests, and his reflection on la littérature-monde en français, these novels perform the mimetic function of literature. Contrast between the rare fantasy threads and the dominant realism makes the author’s particular comment. The object of study is the traditional category of “homeland”, and that’s the way Ben Jelloun’s novels present the sociological and political matters of the contemporary Morocco.